2013
DOI: 10.1080/08927014.2013.808628
|View full text |Cite
|
Sign up to set email alerts
|

Role of hydrophobicity in adhesion of wild yeast isolated from the ultrafiltration membranes of an apple juice processing plant

Abstract: The role of cell surface hydrophobicity in the adhesion to stainless steel (SS) of 11 wild yeast strains isolated from the ultrafiltration membranes of an apple juice processing plant was investigated. The isolated yeasts belonged to four species: Candida krusei (5 isolates), Candida tropicalis (2 isolates), Kluyveromyces marxianus (3 isolates) and Rhodotorula mucilaginosa (1 isolate). Surface hydrophobicity was measured by the microbial adhesion to solvents method. Yeast cells and surfaces were incubated in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 81 publications
0
21
0
Order By: Relevance
“…These results show that C. krusei predominated in biofilms formed on SS disks in both hydrodynamic conditions. In the study by Tarifa et al (2013) C. krusei represented the majority of the isolates from UF membrane samples, showing the adaptive advantage of this species. Brugnoni et al (2007) reported similar results where C. krusei, isolated from a large-scale apple juice processing plant, presented the highest covered surface on SS compared with other yeasts.…”
Section: Biofilm Characterizationmentioning
confidence: 98%
See 4 more Smart Citations
“…These results show that C. krusei predominated in biofilms formed on SS disks in both hydrodynamic conditions. In the study by Tarifa et al (2013) C. krusei represented the majority of the isolates from UF membrane samples, showing the adaptive advantage of this species. Brugnoni et al (2007) reported similar results where C. krusei, isolated from a large-scale apple juice processing plant, presented the highest covered surface on SS compared with other yeasts.…”
Section: Biofilm Characterizationmentioning
confidence: 98%
“…As described in a previous study (Tarifa et al 2013) the resident community on biofouled UF membranes used in the apple juice processing industry was composed of four yeast species. In order to gain an insight into their behavior, a mixture of yeast species was examined under different hydrodynamic forces and exposure times.…”
Section: Biofilm Characterizationmentioning
confidence: 99%
See 3 more Smart Citations